A framework for business model with strategic innovation in ICT firms: The importance of information. Issue 1 (12th March 2018) - Faghih, Nezameddin; Dastourian, Banafsheh; Sajadi, Seyyed Mojtaba; Henten, Andres; Foroudi, Pantea
Abstract : Purpose: The purpose of this study is to help gain an accurate and distinct understanding of information-based business concepts and critical steps in designing an appropriate business model, by providing a framework for designing an innovative information-based business to help fledgling businesses development in the information and communication technology (ICT) industry of Iran. What is a business model framework with the strategic innovation approach in the small and medium enterprises (SMEs) of ICT industry? What are the components of this model and the relations between them? Business model is a logical response to how a business can create value. Changing business environment means that business models are rapidly growing; accordingly, innovation is no longer optional. However, innovation is important in general, but the kind of innovation that is widely and directly dependent on business model will be quite critical for all parts of the organization. In fact, business model innovation is an exquisite technic to create, deliver and earn value by changing one or more components of a typical business model. Business model innovation needs information and form business environment based on dynamic information system. Design/methodology/approach: The present paper focuses upon SMEs in ICT. Grounded theory has been used for this purpose, with 15 interviews conducted. Findings: An emerging market is one in which commercial exchanges of a particular industry between the countries are relatively new but possess great investment attractiveness and a high potential to grow (such as Iran).As the ICT industry of Iran is a leading industry, and the country itself is an emerging market, the main purpose of this study is to provide a framework for designing an innovative information-based business to help fledgling businesses development in the ICT industry of Iran. Originality/value: The purpose of this paper is to help accurate and distinct understanding of the business model concept and critical steps in designing an appropriate business model. Studies conducted to simultaneously deal with the business model and strategic innovations are few, and by the time the proposal was written, there was no research observed from Persian sources.